2020
DOI: 10.3390/genes11111300
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Prognostic Alternative Splicing Signature and Splicing Factors in Lung Adenocarcinoma

Abstract: Analysis of The Cancer Genome Atlas data revealed that alternative splicing (AS) events could serve as prognostic biomarkers in various cancer types. This study examined lung adenocarcinoma (LUAD) tissues for AS and assessed AS events as potential indicators of prognosis in our cohort. RNA sequencing and bioinformatics analysis were performed. We used SUPPA2 to analyze the AS profiles. Using univariate Cox regression analysis, overall survival (OS)-related AS events were identified. Genes relating to the OS-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Multiple studies have confirmed that CELF2 exerts tumour suppressive effects in most tumours, which is significantly increased in developing thymocytes and activated T cells, but its comprehensive understanding within the TME remains unknown 16–26 . Therefore, it is necessary to investigate the relationships between CELF2 expression and TIIC infiltration in the TME.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have confirmed that CELF2 exerts tumour suppressive effects in most tumours, which is significantly increased in developing thymocytes and activated T cells, but its comprehensive understanding within the TME remains unknown 16–26 . Therefore, it is necessary to investigate the relationships between CELF2 expression and TIIC infiltration in the TME.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that CELF2 could regulate multiple steps of RNA processing, such as pre‐mRNA splicing, RNA editing, polyadenylation, mRNA stability and translation 14,15 . Over the past decade, substantial studies have confirmed that CELF2 played a tumour suppressor role in breast cancer, lung cancer, hepatocellular carcinoma, gastric cancer, ovarian cancer, glioma and acute myeloid leukaemia, suggesting that it can be used as a candidate biomarker to predict cancer prognosis 16–23 . Additionally, CELF2 expression was significantly elevated in developing thymocytes and activated T cells and promoted T‐cell receptor expression and signalling through alternative splicing 24–26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA-seq data were analyzed as described previously [ 21 ]. In brief, data quality control at the Q20 level was performed using Trimmomatic [ 22 ], read alignment to the GRCh38 human genome was conducted using HISAT2 [ 23 ], expression was quantified using GENCODE v22 (excluding including mitochondrial genes), and transcripts were normalized into transcripts per million (TPM) using StringTie [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used Trimmomatic for quality control of the RNA-Seq data [ 28 ], as described previously [ 29 ]. For gene expression, the reads that passed quality control were aligned with the GRCh38 human genome using HISAT2 [ 30 ], and featureCounts was used to quantify gene expression with annotation done using GENCODE v22 without mitochondrial genes [ 31 ].…”
Section: Methodsmentioning
confidence: 99%